2016
DOI: 10.1111/fcp.12179
|View full text |Cite
|
Sign up to set email alerts
|

Prescription patterns of antihypertensives in a community health centre in Mexico City: a drug utilization study

Abstract: Hypertension is highly prevalent; in Mexico, the 2012 National Health and Nutrition Survey reported a prevalence of hypertension of 31.5% in the adult population. Pharmacological treatment is the commonest intervention and has been shown to reduce cardiovascular mortality and morbidity, and total mortality. Accordingly, the type and number of antihypertensives used and the outcome — in terms of blood pressure (BP) control — are important. Therefore, our purpose is to learn the pattern of antihypertensive drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
2
15
3
Order By: Relevance
“…CCBs were more frequently used by patients with controlled blood pressure than by patients with uncontrolled blood pressure (66.2% and 55.8%, respectively). This result was in contrast to the result by Alba-Leonel et al 17 , which showed that CCBs had a lower rate of use among individuals with controlled blood pressure than among those with uncontrolled blood pressure (4.8% vs 6.8%, respectively), although that result was insignificant. After adjusting for age, sex, and comorbidities (diabetes mellitus), CCBs were the strongest predictor of blood pressure control at the Tegal Alur II Community Health Center.…”
Section: Discussioncontrasting
confidence: 94%
“…CCBs were more frequently used by patients with controlled blood pressure than by patients with uncontrolled blood pressure (66.2% and 55.8%, respectively). This result was in contrast to the result by Alba-Leonel et al 17 , which showed that CCBs had a lower rate of use among individuals with controlled blood pressure than among those with uncontrolled blood pressure (4.8% vs 6.8%, respectively), although that result was insignificant. After adjusting for age, sex, and comorbidities (diabetes mellitus), CCBs were the strongest predictor of blood pressure control at the Tegal Alur II Community Health Center.…”
Section: Discussioncontrasting
confidence: 94%
“…There was a high prescription of CCB, particularly amlodipine in FCT district hospitals. This was reported in some other studies [11,12,39,40] while CCB has been reported as least prescribed [22,41]. Agents that act on the renin-angiotensin system hold a good share of the prescription, with Lisinopril and Telmisartan leading in the class similar to other studies [15,41].…”
Section: Discussionsupporting
confidence: 71%
“…In a massive study conducted in China during 2004-2007 and 2011-2015, CCB were the first choice of drug followed by BB and ARB/ACEI, respectively. 12,13 In contrast, CCB were found to be least prescribed in a study conducted in northern India, 14 Bangladesh, 15 and Mexico, 16 whereas ARB, ARB, and ACEI were most preferred in these areas, respectively. Studies from Nigeria 17 and Istanbul 18 have shown maximum use of ACEI.…”
Section: Discussionmentioning
confidence: 94%